Estimating the impact of road traffic pricing on residential property values: an investigation of the London congestion charge. (6th September 2011) - Glen, John; Nellis, Joseph G.
A congestion charge was introduced in the centre of London in February 2003. At the outset, the charge was justified by local policy makers on the basis of an expected reduction in car journeys which would result in improvements in environmental amenity, relating to increased journey speeds across all transport modes, reduced accidents and reduced pollution. In so far as this proved to be the case we would expect the improved environmental amenity to be capitalised into increased local residential property values. Simultaneously, vocal 'anti' traffic congestion charge lobbies suggested that the introduction of such a scheme would be detrimental to local residents in terms of increased motoring costs and the inability of road pricing to deliver expected benefits. This paper examines the extent to which these competing influences on residential property values have impacted house prices in Greater London subsequent to the introduction of road pricing.